1961
DOI: 10.1128/jb.81.2.212-217.1961
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Azaserine by Phenylalanine

Abstract: Kaplan, Reilly, and Stock (1959) have studied the reversal of azaserine by aromatic amino acids and have hypothesized without any direct evidence that these substances prevent the binding or penetration of the antibiotic into the cell. The present paper presents more direct evidence that this hypothesis is correct. It is shown that azaserine acts on nongrowing cells of Escherichia coli strain ML35 in such a way that subsequent growth in azaserine-free medium leads to increases in permeability, lysis, and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Previously it was reported that azaserine inhibited the growth of E. coli, and that of all the aromatic amino acids, only L-phenylalanine could reverse this growth inhibition (5,17). There was an inverse relationship between the level of azaserine resistance versus the initial rate of uptake of phenylalanine and the efflux of the amino acid from the cell (16).…”
Section: Discussionmentioning
confidence: 98%
“…Previously it was reported that azaserine inhibited the growth of E. coli, and that of all the aromatic amino acids, only L-phenylalanine could reverse this growth inhibition (5,17). There was an inverse relationship between the level of azaserine resistance versus the initial rate of uptake of phenylalanine and the efflux of the amino acid from the cell (16).…”
Section: Discussionmentioning
confidence: 98%
“…Thus antagonism has not been observed if the required amino acid was supplied as a peptide (PRESCOTT, PETERS & SNELL 1953;HIRSCH & COHEN 1953). Moreover antagonism has not been observed when the cells were first exposed to the one, then to the other amino acid (MATHIESON & CATCHESIDE 1955;BROCK & BROCK 1961). More directly it has been shown by MANDELSTAM (1956) that the inhibiting effect of diamines on the growth of arg: and lys : mutants from Escherichia coli was correlated with their ability to restrict the accumulation of arginine and lysine.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the basis of azaserine uptake via the LIV-I and LS systems, transport studies was carried out using 14 C-labeled two representative substrates, leucine and phenylalanine, in the absence and presence of the probable inhibitor azaserine (0.3-1.2 mM). Strain YG228 (DaroP DbrnQ D(livJ -yhhK-livKHMGF ) DpheP ) carrying pYG218 (pSC101 replicon bla þ livH þ M þ G þ F þ ), which is deficient in uptake of phenylalanine and branched-amino acids [28], was transformed with a mini-F-derived plasmid carrying either the livJ gene (pYG237) or the livK gene (pYG239) [28], and then subjected to transport assays in the presence of 1-10 lM leucine and 10-100 lM phenylalanine.…”
Section: Transport Studiesmentioning
confidence: 99%
“…In earlier works, it was demonstrated that the inhibitory effect of azaserine on E. coli is alleviated effectively in the presence of aromatic amino acids [13], especially phenylalanine [14,15], and partially in the presence of branched-chain amino acids [13]. The alleviating effect of aromatic amino acids on azaserine toxicity could be explained by competition for the uptake of substrates by AroP (a general aromatic amino acid permease with equal affinity to each aromatic amino acid) because all azaserine-resistant mutants isolated so far have lesions in the aroP gene [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation